HUBUNGAN ANTARA EKONOMI DALAM PERENCANAAN KESEHATAN - Muhammad Habibullah Aminy; Sulistianingsih; Bayu Arif Maulana P; Sapta Dwi R; Hilda Sapitri; Romi Hidayatullah; Laela Kamila S; M. Hamzan Hari; Lale Ajeng Khalifatun Wardani (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2022)
Economics and health are very closely related. Economic development greatly affects public health conditions, and improvements in public health conditions will affect work productivity. This article aims to look for economic linkages in health planning. This article is a research based on literature review using the library method. The results show that between health planning and economics there are similarities and linkages. Economic growth and development in a country will greatly affect the health status of its population and is closely related to the country's ability to develop health services and other activities in the health sector. Therefore, policy in the field of health and its implementation is also strongly influenced by macroeconomic considerations.